Sexual and reproductive health service use of unmarried adolescents in Morogoro, Tanzania: insights from a cross-sectional household survey - Morris, Baraka M.; Chombo, Suleiman; Ulrich, Connie M.; Kakoko, Deodatus C. V. (Frontiers in Reproductive Health, 2025)
BackgroundAdolescents in Tanzania represent a dynamic group that significantly influences public health trends, particularly in sexual and reproductive health. Despite the availability of adolescent-friendly sexual and reproductive health services (SRHS), their utilization remains low, especially among unmarried adolescents. This potentially exposes them to risky sexual behaviors, unwanted pregnancies, unsafe abortions, and sexually transmitted infections (STIs), including HIV. This paper examines the use of SRHS by unmarried adolescents in Tanzania and the factors associated with it.MethodsA cross-sectional household survey was conducted over eight months among 312 unmarried adolescents (15–19 years) from Morogoro Municipal and Mvomero District, Tanzania. Data collection utilized the World Health Organization (WHO)-approved Cleland questionnaire, and analysis was performed using STATA 18. To identify factors associated with service utilization, bivariate Chi-square tests and multivariable modified Poisson regression analyses were performed, with significance set at p < 0.05.ResultsAmong 312 unmarried adolescents, 18% had ever used SRH services. Use was significantly higher among those who had worked for pay (aRR = 1.98, p = 0.025) and those with sexual relationship experience (aRR = 2.27, p = 0.007).ConclusionThis paper found persistently low uptake of SRHS among unmarried adolescents in Tanzania, despite strong national policy commitments to improve access. This highlights the gap between policy and the everyday realities of adolescents, shaped by work and relationships. Effective solutions require youth-centered interventions grounded in social spaces, peer networks, and digital platforms to improve service utilization.